Design and Fabrication of Portable Smoke Tunnel for Flow Visualization - Nurhafizah Binti Abdullah, Nurhafizah (Universiti Teknologi Petronas, 2009)
A smoke tunnel design and fabrication is one of the improvement efforts to facilitate the flow visualization for the transparent fluid such as air and water to be visible. The field study of fluid kinematics such as the investigation over immersed model at different Reynolds Numbers and the complexity of flow characteristic when moving or static bodies or structure through a moving fluid also will be takes into consideration. However, wind tunnel and smoke generator which are available in UTP Fluid Mechanics laboratory are not exactly practical to visualizing the air flow pattern appropriately. The methodology of designing and fabricating of the smoke tunnel has been made based on the literature review on previous works or studies. The feasibility study also has been performed for selecting materials which are available in market with cost effective and effortless for construction. The smoke tunnel has been designed based on analysis on air blower characteristics followed by the diffuser length, the test-section cross section area, the contraction cone length, the setting chamber radius inlet, and smoke generator’s tubing. The total length of this tunnel is about 1.6 meters with square test section 0.12 x 0.12 m providing maximum free stream velocity of 23 m/s. The details drawing of the smoke tunnel will be provided through CATIA software for two dimension and three dimension outlines. The design criteria will try to create a good matching between the smoke and the surrounding air flow field by minimizing the difference in the two fluids velocities.